INNOVATIVE DIGITAL SOLUTIONS FOR PROJECT AUCTIONS TO COMBAT INDONESIA'S HOUSING DEFICIT - Haryonugroho, Elisa -; Dinariyana, AAB - (Universitas Pendidikan Indonesia, 2024)
This paper unveils a transformative digital application designed to revolutionize the auction process and tackle Indonesia's pressing housing backlog challenge. Using a structured prototyping approach and innovative tools such as the prototype canvas and validation canvas, the study develops and tests an application to improve the housing procurement process by enhancing user experience and accessibility. Key findings reveal that the app meets critical assumptions and user needs while fostering meaningful communication between project owners and seekers. This research emphasizes the significant impact of usability principles and design thinking in shaping effective digital solutions. Ultimately, this endeavor provides inspiring insights into the potential of digital applications in the housing sector, paving the way for future research and development in this essential field.